Frequency of HIV Positivity in Healthy Blood Donors presenting to a Tertiary Care Hospital - Saria Munir, Zahid Asgher, Masuma Ghazanfar, Maria Qaiser, Kokab Jabeen (Pakistan Journal of Medical & Health Sciences, 2022)
Background: HIV has been under serious consideration by the World Health Organization as well as the Federal government and Provincial health departments. Strict measures have been taken and protocols implemented to curtail the spread of HIV along with Hepatitis B and Hepatitis C. Data from privately-run blood banks have not been reflected in the last 15 years. Aim: To identify current trends of HIV positivity in Lahore Methods: This prospective cross-sectional study was conducted at the Department of Pathology & Laboratory, Doctors Hospital & Medical Centre, Lahore from August 2021 to January 2022. After fulfilling the selection criteria 3160 non-remunerated blood donors selected through non-probability consecutive sampling, were enrolled. Anti-HIV test was performed using chemiluminescence. Results: 3160 voluntary blood donors were investigated. All subjects were males with mean age 29.7 years ranging from 21 years to 46 years. 2 candidates for blood donation (0.06%) were tested positive for HIV. Conclusion: This study reflects stagnation in HIV control as depicted by the frequency of its positivity. There is need to enhance awareness programs in controlling the spread of blood borne diseases especially HIV.